PENERAPAN MODEL PEMBELAJARAN FLIPPED CLASSROOM UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASIALA DAN KEWARGANEGARAAN DI KELAS VIII SMP NEGERI3 MANIAMOLOTAHUNPELAJARAN 2020/2021 - Herman Zagoto; Sitasi Zagoto; Eka Periaman Zai (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2020)
Education is basically a process to help humans develop their potential so that they are able to face the changes that occur. The formulation of the research problem is How is the application of the Flipped Classroom learning model in improving student learning autcomes in pancasila and Citizenship Education subjects in class VIII of SMP Negeri 3 Maniamoloin the 2020/2021 academic year. The research method used is Classroom action research which consists of 2 cycles, and each cycle consists of stages, namely planning, Action, Observation, and Reflection. The aim of the reseacher is to determine the improvement of student learning outcomes. The results show that there is an increase in student learning outcomes after the application of the flipped Learning model Classroom. This can be proven by student lerning outcomes in the second cycle categorized as increasing. It can be conluded that the application of the Flipped Classroom learning model improves student learning outcomes through studens’critical ability to understand the material that has been delivered suggest that teachers of pancasila and civic education subjects should be able to encourage studens’desire to make connections between the material they receive and the real world.